Chapter 3. The place names of Franz Josef Land: framing the problem - Forsberg, Magnus (Septentrio Conference Series, 2015)
A brief introduction to the geographic place names of Franz Josef Land. Franz Josef Land is located in the western Arctic though for much of the 20th Century it was closed behind the Iron Curtain. Prior to that, there were a series of Western expeditions between the ‘official’ discovery in 1873 and the departure of the American Fiala group in 1905. From these expeditions, the islands are heavily connected to the history of the search for the North Pole.